1992
DOI: 10.1111/j.1540-5915.1992.tb00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Attitude, Ambiguity Intolerance and Decision Making: An Exploratory Investigation*

Abstract: Although recent research has identified attitudes towards ambiguity and risk to be important determinants of choice behavior [8] [18], no prior work jointly assessed the roles of both attitudes. We conducted a laboratory experiment using a real decision scenario and conducted exploratory analyses of the relationship between attitudes towards risk and ambiguity and the decision taken by the subjects. The results support the prediction that attitudes towards both risk and ambiguity affect choice behavior. Our ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 34 publications
0
22
0
2
Order By: Relevance
“…To compound the issue, few researchers have examined whether or not risk and uncertainty are distinct constructs (e.g., Ghosh & Ray, 1992, 1997. Untangling the confusion between the two constructs and integrating them into an appropriate decisionmaking model would be helpful in assessing their influences on people's travel behavior.…”
Section: Introductionmentioning
confidence: 98%
“…To compound the issue, few researchers have examined whether or not risk and uncertainty are distinct constructs (e.g., Ghosh & Ray, 1992, 1997. Untangling the confusion between the two constructs and integrating them into an appropriate decisionmaking model would be helpful in assessing their influences on people's travel behavior.…”
Section: Introductionmentioning
confidence: 98%
“…Prior research has shown that whether the actual outcomes are seen as good or bad may affect managers' attitude toward taking risks 2 (Kahneman and Tversky, 1979) and their attitude toward ambiguity (Kahn and Sarin, 1988;Ghosh and Ray, 1992). Similarly, whether variances are above or below the interval benchmark may also affect managers' attitude toward ambiguity and their risk attitude.…”
mentioning
confidence: 95%
“…Finally, this research explores the link between a psychological measure of "intolerance of ambiguity" and the conventional economic measure. Sherman (1974), as well as Gosh and Ray (1992) for instance, found a modest correlation between Budner's psychological scale of "Intolerance of Ambiguity" and ambiguity aversion. Table I below summaries the predictions regarding insurers behaviours.…”
Section: Introductionmentioning
confidence: 99%